Autoimmune Encephalitis in Long-Standing Schizophrenia: A Case Report - Vaux, Amy; Robinson, Karen; Saglam, Burcu; Cheuk, Nathan; Kilpatrick, Trevor; Evans, Andrew; Monif, Mastura (Frontiers in Neurology, 2022)
Anti-N-methyl-D-aspartate (NMDA) receptor antibody (anti-NMDAR Ab)-mediated encephalitis is an autoimmune disorder involving the production of antibodies against NMDARs in the central nervous system that leads to neurological or psychiatric dysfunction. Initially described as a paraneoplastic syndrome in young women with teratomas, increased testing has found it to be a heterogeneous condition that affects both the sexes with varying clinical manifestations, severity, and aetiology. This case report describes a 67-year-old man with a 40-year history of relapsing, severe, treatment-refractory schizophrenia. Due to the worsening of his condition during a prolonged inpatient admission for presumed relapse of psychosis, a revisit of the original diagnosis was considered with extensive investigations performed including an autoimmune panel. This revealed anti-NMDAR Abs in both the serum and cerebrospinal fluid on two occasions. Following treatment with intravenous immunoglobulin and methylprednisolone, he demonstrated rapid symptom improvement. This is a rare case of a long-standing psychiatric presentation with a preexisting diagnosis of schizophrenia subsequently found to have anti-NMDAR Ab-mediated encephalitis. Whether the case is one of initial NMDAR encephalitis vs. overlap syndrome is unknown. Most importantly, this case highlights the need for vigilance and balanced consideration for treatment in cases of long-standing psychiatric presentation where the case remains treatment refractory to antipsychotics or when atypical features including seizures and autonomic dysfunction or focal neurology are observed.